2013
DOI: 10.1186/1477-7819-11-113
|View full text |Cite
|
Sign up to set email alerts
|

Bronchioloalveolar invasion in non-small cell lung cancer is associated with expression of transforming growth factor-β1

Abstract: BackgroundAdenocarcinoma in situ (AIS) and minimally invasive adenocarcinoma (MIA) with fibrous stromal invasion are newly introduced subtypes of small lung adenocarcinoma. AIS is a small localized adenocarcinoma in which growth is restricted to neoplastic cells along preexisting alveolar structures without fibrous stromal invasion. In MIA, by contrast, tumor cells have infiltrated the myofibroblastic stroma. Transforming growth factor (TGF)-β is known to be produced by progressor tumors, and excessive TGF-β c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…Further, this study for the first time showed that miR‐9 knockdown suppressed NSCLC cell invasion and adhesion in vitro . TGF‐β1 is an important regulator in NSCLC metastasis . In the present study, we found TGF‐β1‐induced cell invasion and adhesion were also inhibited by miR‐9 knockdown.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Further, this study for the first time showed that miR‐9 knockdown suppressed NSCLC cell invasion and adhesion in vitro . TGF‐β1 is an important regulator in NSCLC metastasis . In the present study, we found TGF‐β1‐induced cell invasion and adhesion were also inhibited by miR‐9 knockdown.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, SOX7 protein expression was regulated by miR‐9. TGF‐β1 has been implicated in the pathogenesis of lung cancers . Interestingly, in the present study, we found the expression of miR‐9 and SOX7 was up‐regulated by TGF‐β1 treatment in NSCLC cells, despite the observation that SOX7 was a direct target of miR‐9.…”
Section: Discussioncontrasting
confidence: 53%
“…Therefore, the prevention and treatment of mutant gene has an important significance. Recent studies showed, TGF-β could increase the invasiveness of cancer cells by increasing their proteolytic activity and promoting their binding to cell-adhesion molecules (Imai et al, 2013). In an earlier study, tumor-derived TGF-β1 induced dendritic cell apoptosis within lymph nodes in non-small cell lung cancer (Imai et al, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies showed, TGF-β could increase the invasiveness of cancer cells by increasing their proteolytic activity and promoting their binding to cell-adhesion molecules (Imai et al, 2013). In an earlier study, tumor-derived TGF-β1 induced dendritic cell apoptosis within lymph nodes in non-small cell lung cancer (Imai et al, 2013). Consistent with those findings, the effects of TGF-β1 on angiogenesis, stroma formation and immune function appear to further support tumor progression and invasion (Balasubramanian et al, 2002;Botaitis et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…TGFb-induced expression of IGFBP-3 regulates IGF-I receptors signalling in human osteosarcoma cells [134]. Bronchioloalveolar invasion in NSCLC is associated with tumours expression of TGFb1 assessed with immunohistochemical staining using anti-TGFb1 antibody [135]. It was also found a higher concentration of TGFb1 (4.2 x) and TGFb2 (1.5 x) (but not TGFb3) in the blood of patients with metastatic malignant melanoma in contrast to the initial development chase which indicates a systemic immunosuppressive TGFb1 activity in the terminal stage of the disease [136].…”
Section: Prace Poglądowementioning
confidence: 99%